Ethnographic Theology - Wigg-Stevenson, N. author. aut Link
X, 210 p.
Keywords: This book uses ethnography as theological practice, yielding a theology constructed at the intersection of church, academy and everyday life. Drawing on the author's research in her Baptist church, the resulting 'ethnographic theology' produces creative theological insights, while also proposing fresh alternatives for Christian thought and action.